2020
DOI: 10.1002/anie.202004977
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Activity of Iron Peroxo Porphyrin Intermediates in the Reaction Layer during the Electrochemical Reductive Activation of O2

Abstract: Herein we report the first example of using scanning electrochemical microscopy (SECM) to quantitatively analyze O2 reductive activation in organic media catalyzed by three different Fe porphyrins. For each porphyrin, SECM can provide in one single experiment the redox potential of various intermediates, the association constant of FeII with O2, and the pKa of the FeIII(OOH−)/ FeIII(OO2−) couple. The results obtained can contribute to a further understanding of the parameters controlling the catalytic efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Noel et al also observed a similar redox couple for Fesuperoxo species within the similar potential range. 69 Therefore, based on the CV experiment, it can be said that the Fe 2 O 3 -Y catalyst interacted with peroxymonosulfate to form a Fe-peroxo or Fe-superoxo intermediate species.…”
Section: Mechanism Of the Trimerization Of Indoles In The Presence Of...mentioning
confidence: 99%
“…Noel et al also observed a similar redox couple for Fesuperoxo species within the similar potential range. 69 Therefore, based on the CV experiment, it can be said that the Fe 2 O 3 -Y catalyst interacted with peroxymonosulfate to form a Fe-peroxo or Fe-superoxo intermediate species.…”
Section: Mechanism Of the Trimerization Of Indoles In The Presence Of...mentioning
confidence: 99%
“…Electroactive RIS are more often probed directly, where they are created using the generation collection mode (G/C) of the SECM. In this mode, inherited from the ring-disk electrode configuration, a generator electrode, G, triggers a reaction of interest while the collector one, C, facing G, collect the RIS produced at G. Figure 1a illustrates the substrate generation/tip collection (SG/TC) of Fe III (OO 2-) intermediates of ms lifetime produced during O 2 reductive activation at iron porphyrins [10]. The reverse configuration (tip generation, substrate collection mode, TG/SC) was also employed with gap distances from 10µm to 500nm, using a classical or an hemispherical UME [11], or even down to 73 nm employing nanoelectrodes (nanoSECM) [12].…”
Section: Secm Modes Used For the Detection Of Reactive Intermediate S...mentioning
confidence: 99%
“…This route too faces different challenges such as reducing the active metal-(hydro)peroxo intermediates or intermolecular reactions leading to unreactive bridged oxo metal complexes. 6,21–30…”
Section: Introductionmentioning
confidence: 99%
“…This route too faces different challenges such as reducing the active metal-(hydro)peroxo intermediates or intermolecular reactions leading to unreactive bridged oxo metal complexes. 6,[21][22][23][24][25][26][27][28][29][30] An alternative route to develop more sustainable processes relies on the coupling of a photoredox module and a molecular transition metal catalyst for photocatalytic OAT reactions. [31][32][33][34][35][36][37][38][39][40][41][42][43] The activation of O 2 through light-induced electron transfer provides a unique opportunity to generate these reactive oxo and peroxo species in a benign and controlled manner.…”
Section: Introductionmentioning
confidence: 99%